PENGARUH TINGKAT RASIO PROFITABILITAS DAN TINGKAT RASIO SOLVABILITAS TERHADAP RETURN SAHAM DENGAN PENGUNGKAPAN RESIKO SEBAGAI VARIABEL MODERATOR (STUDI KASUS PADA PERUSAHAAN BERKATEGORI LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010 – 2013) - Linda Lestari Krisnawati (Jurnal Akuntansi Manajerial (Managerial Accounting Journal), 2017)
This research is a study about "The Effects of Profitability Ratios And Solvency Ratios of the Stock Returns Moderated By Risk Disclosure In Companies listed in LQ45 during 2010-2013". The dependent variable in this study is Stock Returns, while the independent variable is Profitability Ratios And Solvency Ratios. Moderating variables using variable application of Risk Disclosure. Population of this study  are companies registered in LQ45  during 2010-2013. There are 146 companies as a samples that fullfill  the criteria. The method of data analysis which is used in this research is multiple regression analysis. Before to the regression analysis is conducted, the descriptive statistical analysis and test of the classical assumptions have meetly done . The results of this study partially approve that the variable Profitability Ratios significant effect on stock returns, while Solvency Ratios significantly influence the stock return. Simultaneously, the Variables of Profitability Ratios And Solvency Ratios have a significant effect on Stock Return. Moderation Application of risk disclosre did not effect the Profitability Ratios of stock return. Moderation Application of risk disclosre is strengthen the influence effect of the Solvancy Ratios of stock return but no significant.